2004
DOI: 10.1039/b311852e
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio and NMR studies on the effect of hydration on the chemical shift of hydroxy protons in carbohydrates using disaccharides and water/methanol/ethers as model systems

Abstract: Density functional theory (DFT) and Hartree-Fock (HF) quantum mechanical calculations have been performed on the disaccharides, [small beta]-l-Fucp-(1[rightward arrow]4)-[small alpha]-d-Galp-OMe, [small beta]-l-Fucp-(1[rightward arrow]4)-[small alpha]-d-Glcp-OMe, and [small beta]-l-Fucp-(1[rightward arrow]3)-[small alpha]-d-Glcp-OMe. The [capital Delta][small delta]-values (difference between the chemical shift in the disaccharide and the corresponding monosaccharide methyl glycoside) for the exchangeable hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 25 publications
1
26
0
1
Order By: Relevance
“…28 To summarize, the upfield shifts of the GlcNAc 3-OH group are probably caused by the nearby ring and glycosidic O atoms as described for structures with a similar structural arrangement. [11][12][13][14][15][16] The shielding of Gal 4-OH when reducing the 2-C atom in 3 and 4 can only be attributed to a significant change in the water network covering the carbohydrate, since no direct interaction between 2-OH and 4-OH is possible. In addition, the large downfield shift introduced to some OH groups when introducing a NH 3 þ group at Gal 6-C (11 and 12) is likely to be caused by the positive charge, since the effect is only observed on adjacent groups and decreases with the distance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…28 To summarize, the upfield shifts of the GlcNAc 3-OH group are probably caused by the nearby ring and glycosidic O atoms as described for structures with a similar structural arrangement. [11][12][13][14][15][16] The shielding of Gal 4-OH when reducing the 2-C atom in 3 and 4 can only be attributed to a significant change in the water network covering the carbohydrate, since no direct interaction between 2-OH and 4-OH is possible. In addition, the large downfield shift introduced to some OH groups when introducing a NH 3 þ group at Gal 6-C (11 and 12) is likely to be caused by the positive charge, since the effect is only observed on adjacent groups and decreases with the distance.…”
Section: Discussionmentioning
confidence: 99%
“…Positioning of the 3-OH proton in close proximity to the Gal ring and the glycosidic O has been found to provide a shielding effect. 15 In lactose and compounds with similar stereochemistry and conformation around the glycosidic linkage, such a close proximity renders possibly the formation of a hydrogen bond between Gal 5-O and Glc 3-OH. 22 The effects observed for GlcNAc 2-NH and GlcNAc 6-OH are weaker.…”
Section: Chemical Shifts D and Chemical Shift Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…The results suggested that in strongly hydrated systems, the interaction between bulk water and hydroxy protons is the key factor contributing to the values of chemical shifts. 8 Thus, when the hydration of a hydroxy group is reduced due to interaction with acetal oxygens or to steric factors, the hydroxy proton is shielded.…”
mentioning
confidence: 99%